Should robots be taxed? - Guerreiro, João (2022)
Using a quantitative model that features technical progress in automation and endogenous skill choice, we show that, given the current U.S. tax system, a sustained fall in automation costs can lead to a massive rise in income inequality. We characterize the optimal tax system in this model. We find that it is optimal to tax robots while the current generations of routine workers, who can no longer move to non-routine occupations, are active in the labour force. Once these workers retire, optimal robot taxes are zero.